ESCMID Study Group for Infections in Compromised Hosts (ESGICH) Consensus Document on the safety of targeted and biological therapies: an infectious diseases perspective (Introduction). (June 2018) - Fernández-Ruiz, M.; Meije, Y.; Manuel, O.; Akan, H.; Carratalà, J.; Aguado, J.M.; Delaloye, J.
Abstract: Background: The field of new biological agents is increasing exponentially over the past years, thus making prevention and management of associated infectious complications a challenge for nonspecialized clinicians. Aims: The present consensus document is an initiative of the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Infections in Compromised Hosts (ESGICH) aimed at analysing, from an infectious diseases perspective, the safety of targeted and biological therapies. Sources: Computer-based Medline searches with MeSH terms pertaining to each agent or therapeutic family. Content: The document is structured in sections according to the targeted site of action of each drug class: proinflammatory cytokines; interleukins, immunoglobulins and other soluble immune mediators; cell surface receptors and associated signaling pathways; intracellular signaling pathways; lymphoma and leukaemia cells surface antigens; and other targeted therapies. A common outline is followed for each agent: summary of mechanism of action, approved indications and common off-label uses; expected impact on the host's susceptibility to infection; available clinical evidence (i.e. pivotal clinical trials, postmarketing studies, case series and case reports); and suggested prevention and risk minimization strategies. The methodologic and practical difficulties of assessing the specific risk posed by a given agent are also discussed. Implications: This ESGICH consensus document constitutes not only a comprehensive overview of the molecular rationale and clinical experience on the risk of infection associated with approved targeted therapies but also an attempt to propose a series of recommendations with the purpose of guiding physicians from different disciplines into this emerging framework.